Capacitance model for magnetic devices - Dürbaum, Thomas (PESC Record - IEEE Annual Power Electronics Specialists Conference, 2000)
Magnetic components are essential for switched-mode power supplies. The designer has to understand the parasitic behaviour of these nonstandard devices. Besides the losses and leakage inductance a model should include the capacitive behaviour. The flat model describes the electrostatics of magnetics consisting of two layers. This paper demonstrates the extension towards an arbitrary number of layers. It will be shown how the resulting large number of capacitors in case of the layer based capacitance model can analytically be reduced to the minimum number needed for a correct description.
UnivIS-Import:2015-03-09:Pub.2000.tech.IE.lselek.capaci_3